Protection of the Weak Party of the Banking Contract in the Case of Using Smart Contract - E. P. Volos (Теоретическая и прикладная юриспруденция)
The article is devoted to the features of protection the weak party in the situation when the parties to the banking agreement use the “smart contract” technology from the point of view of Russian and foreign doctrine. The author proposes particular changes and additions to the current regulation and the established judicial practice, while the general principles of legislation remain unchanged.